2015
DOI: 10.1051/0004-6361/201526125
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a magnetic field in a differentially rotating radiative zone

Abstract: Context. Recent spectropolarimetric surveys of main-sequence intermediate-mass stars have exhibited a dichotomy in the distribution of the observed magnetic field between the kG dipoles of Ap/Bp stars and the sub-Gauss magnetism of Vega and Sirius. Aims. We would like to test whether this dichotomy is linked to the stability versus instability of large-scale magnetic configurations in differentially rotating radiative zones. Methods. We computed the axisymmetric magnetic field obtained from the evolution of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 32 publications
4
28
0
Order By: Relevance
“…For examples of the (rather complex) interactions possible, see Mestel et al (1988), Moss et al (1990), or Wei and Goodman (2015). Most recently, Gaurat et al (2015) have investigated the dichotomy between the strong "Ap-type" fields and the sub-gauss magnetism observed in other cases, and argued (similarly to Aurière et al 2007;Lignières et al 2014) that the lower bound of observed field strengths in stably stratified stars might arise essentially from a stability condition: strong enough fields are stable and persist, while weaker ones decay quickly. In all cases, a central role is played by whether the field configurations are stable for intervals comparable to the main-sequence lifetime of the star, so we turn to that topic next.…”
Section: How Strong Should Fossil Fields Be?mentioning
confidence: 99%
See 1 more Smart Citation
“…For examples of the (rather complex) interactions possible, see Mestel et al (1988), Moss et al (1990), or Wei and Goodman (2015). Most recently, Gaurat et al (2015) have investigated the dichotomy between the strong "Ap-type" fields and the sub-gauss magnetism observed in other cases, and argued (similarly to Aurière et al 2007;Lignières et al 2014) that the lower bound of observed field strengths in stably stratified stars might arise essentially from a stability condition: strong enough fields are stable and persist, while weaker ones decay quickly. In all cases, a central role is played by whether the field configurations are stable for intervals comparable to the main-sequence lifetime of the star, so we turn to that topic next.…”
Section: How Strong Should Fossil Fields Be?mentioning
confidence: 99%
“…In some cases these simply shape a pre-existing field, whereas in others it may be that dynamo action is possible. Various authors have investigated these interactions using 2-D and 3-D simulations; among them, we note the papers by , Zahn et al (2007), Arlt and Rüdiger (2011), and the very recent simulations of Jouve et al (2015) and Gaurat et al (2015).…”
Section: Evolution Of Magnetism In Stable Layersmentioning
confidence: 99%
“…In an attempt to interpret this division, Aurière et al (2007) proposed a scenario based on the stability of a large scale magnetic configuration in a differentially rotating star, leading to estimating a critical field strength above which magnetic fields can remain stable on long time scales, while magnetic fields below this limit would likely be destroyed by the internal shear. More detailed models including 2D and 3D numerical simulations Gaurat et al 2015) tend to confirm the existence of a critical field in such configurations, where the pre-main sequence contraction is a possible way to force differential rotation. On the other hand, the magnetic dichotomy might simply be the result of two different magnetic field generation processes.…”
Section: Introductionmentioning
confidence: 96%
“…This has lead them to be referred to as fossil fields. The first theory consists of frozen-in magnetic fields originally present in the interstellar medium during the collapse of the pre-stellar cloud (Moss et al 2001), while the other consists of relaxing the dynamo field that is created during the pre-main sequence (PMS) convective phase in stars that meet specific conditions related to A&A 622, A72 (2019) their rotation (Duez & Mathis 2010;Braithwaite & Spruit 2004;Emeriau & Mathis 2015;Gaurat et al 2015). In this paper, we do not focus on the first scenario, and instead derive new observational constraints to the second scenario by measuring the rotational and magnetic properties of HAeBe and A/B stars' progenitors: the intermediate-mass T Tauri stars (IMTTS).…”
Section: Introductionmentioning
confidence: 99%